2016
DOI: 10.1093/pcp/pcw005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Framework of Male Gametogenesis in the LiverwortMarchantia polymorphaL.

Abstract: In land plants, there are two types of male gametes: one is a non-motile sperm cell which is delivered to the egg cell by a pollen tube, and the other is a motile sperm cell with flagella. The molecular mechanism underlying the sexual reproduction with the egg and pollen-delivered sperm cell is well understood from studies using model plants such as Arabidopsis and rice. On the other hand, the sexual reproduction with motile sperm has remained poorly characterized, due to the lack of suitable models. Marchanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 59 publications
2
101
0
Order By: Relevance
“…When entering the sexual reproductive phase, the male and female gametophytes develop individual sexual organs, the antheridium and archegonium, on special gametophores called the antheridiophore and archegoniophore, respectively45. It has been shown that a number of specific genes are expressed in the antheridium of M. polymorpha 41. In our Mp CAPE promoter- GUS experiment, the promoter activity was specifically detected in the antheridium (Fig.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…When entering the sexual reproductive phase, the male and female gametophytes develop individual sexual organs, the antheridium and archegonium, on special gametophores called the antheridiophore and archegoniophore, respectively45. It has been shown that a number of specific genes are expressed in the antheridium of M. polymorpha 41. In our Mp CAPE promoter- GUS experiment, the promoter activity was specifically detected in the antheridium (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…The fact that AC has a dominant function in sperm physiology and has been genetically inherited during the evolution of mammals may suggest a possible role for cAMP in the reproductive organ development of M. polymorpha . A recent paper has shown the expression of a cAMP-dependent protein kinase and cyclic nucleotide-gated ion channel in the antheridium of M. polymorpha 41. It is likely that these proteins function as signalling factors downstream of MpCAPE.…”
Section: Discussionmentioning
confidence: 99%
“…SCs divide both transversely and vertically, eventually giving rise to numerous sperm mother cells (SMCs). An SMC divides diagonally to form two triangular spermatids, which then differentiate into flagellated sperm cells (Figure 2A) [21,22]. By contrast, multiple archegonia are formed below the lobes of each archegoniophore via tightly regulated cell-division sequences ( Figure 2B).…”
Section: Rkd Genes Are Associated With Land Plant Reproductionmentioning
confidence: 99%
“…Due to their small size, P. patens antheridia can be easily fixed and observed as whole-mount samples without the requirement for microscopic sections e.g. performed of M. polymorpha antheridia [25]. In particular the attachment of released spermatozoids to polylysine-coated slides considerably reduces the necessary preparation time for the observation of sperms.…”
Section: Resultsmentioning
confidence: 99%
“…While the light-microscopic analysis of the sperms is documented in many moss species, e.g. [19–24], and has become a recent focus in the liverwort Marchantia polymorpha [25, 26], the methodology is not established for P. patens . We assume the lack of detailed protocols is the major obstacle preventing research on P. patens sperms and discuss possible reasons so far hindering the establishment of suitable protocols.…”
Section: Introductionmentioning
confidence: 99%